PENGEMBANGAN MODEL TEKNOLOGI PENJUALAN TERINTEGRASI BERBASIS APLIKASI MOBILE UNTUK MEMPERMUDAH AKSES DAN TRANSAKSI BAGI KONSUMEN GLOBAL TERHADAP PRODUK UMKM - Saragih, Roy Sahputra; Damanik, Erikson; Sugara, Heru (Politeknik Bisnis Indonesia, 2024)
This study aims to develop an integrated sales technology model based on a mobile application that can improve the competitiveness of MSME products in Pematang Dolok Kahean Village in the global market. Pematang Dolok Kahean Village has the potential for superior products, such as snacks and handicrafts, but is still limited in terms of market access and utilization of marketing technology. Traditional marketing, such as through local markets and exhibitions, cannot reach a wider market, both nationally and internationally. The stages of this research begin with identifying the needs of MSMEs in the village, followed by designing an application model that is in accordance with the characteristics of the product and the target market. Furthermore, a prototype of a mobile application was developed that integrates easy and secure product management, ordering, and payment features. Using this technology model can increase efficiency in product management and transactions, while also making it easier for consumers to buy MSME products from outside the region. The implementation of this technology model can provide practical solutions that support increasing market access, expanding distribution networks, and encouraging local economic growth through more competitive sales of MSME products.